2004
DOI: 10.1111/j.1541-1338.2004.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Old Pictures in New Frames: Issue Definition and Federal Arts Policy

Abstract: Over the past three decades, those advocating for arts funding have shifted their arguments. When the National Endowment of the Arts (NEA) was created in 1965, its supporters praised arts and culture for their uplifting qualities, and for their ability to counterbalance trends toward materialism and militarism. By the 1990s, arts advocates were far more likely to use instrumentalist arguments, showing that investment in arts and culture produce other desirable benefits, most notably economic development advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…The lower levels of legitimacy might have been an incentive for the NEA to publish policy reports more often than their European counterparts. Research on the discourse used in Congressional debates on arts funding from 1965-1995 has shown that ethnic diversity strongly resonates in the American political field (Strom and Cook 2004). 18 In line with legitimacy theory, the results of my analyses show clear peaks in the amount of ethnic discourse during these legitimacy crises (see Figure 2).…”
Section: ------------------------------supporting
confidence: 58%
“…The lower levels of legitimacy might have been an incentive for the NEA to publish policy reports more often than their European counterparts. Research on the discourse used in Congressional debates on arts funding from 1965-1995 has shown that ethnic diversity strongly resonates in the American political field (Strom and Cook 2004). 18 In line with legitimacy theory, the results of my analyses show clear peaks in the amount of ethnic discourse during these legitimacy crises (see Figure 2).…”
Section: ------------------------------supporting
confidence: 58%
“…The shift toward local cultural policy is relevant not only for the change in the level of government involved in the policy process but also in the policy model and the definition of arts and culture (Strom and Cook 2004). The former model was based on the need to subsidize arts and culture for their intangible worth; the new paradigm highlights the economic development impact generated by arts and culture in their communities (Florida 2002a;Cohen, Schaffer, and Davidson 2003;Markusen 2006) and shows how arts and culture can offer a variety of local assets that can be engines of urban revitalization (Whitt, Stone, and Sanders 1987;Strom 2002Strom , 2008Strom , 2003Gray 2007;Stern and Seifert 2007 ).…”
Section: Studying the Context Of Urban Cultural Policymentioning
confidence: 99%
“…Briefly, scholars have identified three general sets of sources influencing the contours of how a problem is socially constructed and defined. The first is a set of macro-level conditions that relate to broader societal concerns and values (Strom and Cook 2004). The second includes micro-level human dispositions such as how an individual processes information and how he or she forms an opinion relative to broaderlevel concerns (Zaller 1992).…”
Section: Problem Definitionsmentioning
confidence: 99%
“…These scholars assume that micro-level variables impact macro-level values and vice versa (Kay 2003). Strom and Cook's (2004) study of how arts advocates redefined the value of arts to federal policy-makers demonstrates how problem definitions, in order to maintain their effectiveness, must be responsive to changes in the macro political environment (Pralle 2006b). In other words, its social construction must reflect a larger political context.…”
Section: Problem Definitionsmentioning
confidence: 99%